ASA ESA: A DANCE PERFORMANCE REPRESENTING THE TRIDATU SYMBOL IN BALINESE HINDU COSMOLOGY - Prabhawita, Gita; Miftakhul Hauna; Mega Cantik Putri Aditya (Institut Seni Indonesia Denpasar, 2025)
Asa Esa is a Balinese contemporary dance performance inspired by the sacred Tridatu thread, a symbolic element deeply rooted in Balinese Hindu society. The Tridatu symbolizes the Tri Murti in Balinese Hindu cosmology, representing the unity of three principal deities. This study aims to analyze how the symbolism of the Tridatu is manifested through choreography, music, visual design, and collaborative elements, thereby bridging spiritual values with contemporary artistic expression. The creative process follows Alma M. Hawkins’ method of exploration, improvisation, and performance. Data were collected through literature review, interviews, and observations of Balinese Hindu religious practices. The movement vocabulary combines traditional Balinese dance with contemporary techniques, while the use of lighting, costume, and visual design emphasize the symbolic essence of the Tridatu. The work originates from the exploration of intertwined threads that gradually unravel, evoking multiple layers of spiritual interpretation. Asa Esa represents the belief in spiritual unification embodied in the Tridatu. The findings reveal that the work synthesis of tradition and innovation, conveying symbolic meaning through movement, music, makeup, and stage design, while maintaining both aesthetic and spiritual harmony. The implications highlight the potential of performing arts as a medium for cultural preservation, philosophical reflection, and spiritual communication grounded in local wisdom.